2022
DOI: 10.4049/jimmunol.2200079
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine, Fatty Acids, and Lipid Mediators Are Linked to COVID-19 Severity

Abstract: on behalf of the ImmunoCOVID Brazilian Research Consortium 3Lipid and cholinergic mediators are inflammatory regulators, but their role in the immunopathology of COVID-19 is still unclear. Here, we used human blood and tracheal aspirate (TA) to investigate whether acetylcholine (Ach), fatty acids (FAs), and their derived lipid mediators (LMs) are associated with COVID-19 severity. First, we analyzed the perturbation profile induced by SARS-CoV-2 infection in the transcriptional profile of genes related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 87 publications
6
15
0
7
Order By: Relevance
“…To understand the reciprocal influence of cytokines and sHLA-G levels, we performed several correlational analyses among these soluble molecules. As observed in this study and others, IL-6, IL-8 and IL-10 have systematically been reported as increased in COVID-19, particularly in the acute phase of the disease [ 49 ]. Considering that sHLA-G levels were increased in COVID-19 patients, irrespective of disease severity, the increased sHLA-G levels occurred together with the currently reported inflammatory IL-6, IL-8, and IL-10 cytokines, and positive correlations were observed between sHLA-G and these cytokines; only IL-10 has a well-recognized role on the induction of the HLA-G gene expression [ 50 ].…”
Section: Discussionsupporting
confidence: 78%
“…To understand the reciprocal influence of cytokines and sHLA-G levels, we performed several correlational analyses among these soluble molecules. As observed in this study and others, IL-6, IL-8 and IL-10 have systematically been reported as increased in COVID-19, particularly in the acute phase of the disease [ 49 ]. Considering that sHLA-G levels were increased in COVID-19 patients, irrespective of disease severity, the increased sHLA-G levels occurred together with the currently reported inflammatory IL-6, IL-8, and IL-10 cytokines, and positive correlations were observed between sHLA-G and these cytokines; only IL-10 has a well-recognized role on the induction of the HLA-G gene expression [ 50 ].…”
Section: Discussionsupporting
confidence: 78%
“…In the same line, eicosanoids such as cys‐LTs, PGE 2 , and LTB 4 are also released by ATP and HMGB1 stimuli 18,41–43 . In agreement, some data in the literature demonstrated that lipid mediators were increased in patients with severe COVID‐19 and may be associated with poor outcomes 31,44 . Meanwhile, the role of eicosanoids in COVID‐19 remains to be characterized.…”
Section: Discussionmentioning
confidence: 59%
“…Not only metabolites but also lipids such as carnitines and phosphatidylcholine ( Caterino et al, 2021b ; D’alessandro et al, 2021 ; Wu et al, 2022 ) and an NMR-determined pro-atherogenic lipoprotein profile have been associated to COVID-19 severity ( Schmelter et al, 2021 ; Rendeiro et al, 2022 ). In addition, the metabolic changes associated with severity are also correlated with immune response markers: between plasma oxylipins ( Karu et al, 2022 ) or acetylcholine ( Pérez et al, 2022 ) with chemokines/neutrophiles or between lysophosphatidyl choline (LPC) with IL-6 ( Sindelar et al, 2021 ).…”
Section: Biomarkers Of Covid-19 Severitymentioning
confidence: 99%